2022
DOI: 10.1007/s10639-022-11023-6
|View full text |Cite
|
Sign up to set email alerts
|

Nomophobia among Preservice Teachers: a descriptive correlational study at Ghanaian Colleges of Education

Abstract: The present study aimed at investigating nomophobia prevalence, thus, recurrence of anxiety without a smartphone, with preservice teachers in the Colleges of Education, Ghana. An actual sample of 345 preservice teachers responded to a 20-item questionnaire on nomophobia (NMP-Q). A one-way MANOVA between different groups statistics was applied in determining the differences in nomophobic behaviours among preservice teachers based on non-technology-related variables (gender, age, specialism, subjective economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Our findings suggest that longer daily mobile phone use was significantly associated with nomophobia. In line with our finding, a bidirectional relationship between nomophobia and duration of daily mobile phone use was also seen previously [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings suggest that longer daily mobile phone use was significantly associated with nomophobia. In line with our finding, a bidirectional relationship between nomophobia and duration of daily mobile phone use was also seen previously [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…This particular finding implies that the prevalence of nomophobia is a serious problem among office workers. Similarly, a study conducted in Ghana among teachers revealed that all participants exhibited nomophobic behaviors, but with the highest percentage being observed for a Moderate level of nomophobia (54.8%) (Essel et al, 2022). Likewise, a study conducted in Turkey among pre-service teachers indicated that all participants experienced nomophobia, with 22% were categorized as Mild nomophobia, 55.5% exhibited Moderate nomophobia (Sevim-Cirak and Islim, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…There is evidence in the literature corroborating with this finding. Previous studies have revealed that the nomophobia levels of university students are at moderate and above levels (e.g., Adnan & Gezgin, 2016;Gezgin & Çakır, 2016;Essel, et al, 2022). We measured the in-service preschool teachers' and the preschool teacher candidates' levels of FoMO at moderate level.…”
Section: Discussionmentioning
confidence: 98%